PRACTICALITY E-MODULE OF VIBRATION IN EVERYDAY LIFE ON ONLINE LEARNING TO IMPROVE SCIENCE PROCESS SKILLS OF GRADE X HIGH SCHOOL STUDENTS - Aditya Fahlevi; - Asrizal; - Gusnedi; - Hidayati (Universitas Negeri Padang, 2021)
The development of 21st century skills can be done through the discipline of physics. Physics learning in schools has a central role in providing learners with 21st century skills. One of the lessons that can develop students' skills and stimulate students to be active and creative is learning with a science process skills approach. The learning process involves more students acting more actively, as well as managing findings derived from aspects of skills. From the initial studies conducted it was found that students' science process skills in online learning to have a variety of problems. One alternative to problem solving is to develop electronic modules (e-modules) to improve students' process skills. The methodology used in this research is Research and Development (R&D). The model used is the R&D research model according to Sugiyono in 2012. The object of this research is the e-module vibration in everyday life in online learning. The data collection instrument used was a practicality questionnaire. The practicality test instrument consists of four components, it is usability, ease of use, attractiveness, and clarity. The results of the practicality assessment were analyzed based on the interpretation criteria of the scores obtained. Based on the research objectives and data analysis carried out, it was obtained the average value of e-module practicality which was developed according to the teacher, which was 94.5 in the very good category and the average value of e-module practicality according to the students got a value of 90.5 in very good category.